2009
DOI: 10.1007/s10974-009-9167-z
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein content influences both growth and size distribution of anterior and posterior muscle fibres in juveniles of Pagellus bogaraveo (Brunnich)

Abstract: Muscle cellularity was studied in Pagellus bogaraveo juveniles fed on diets with different protein contents. Measured in transversal body sections, at both post-opercular and post-anal locations, the morphometric variables estimated were: total muscle area (A), total number of fibres (N), number of fibres per unit area of muscle (N A ) and cross-sectional fibre area ð" aÞ; of the two main muscle fibre types. At the end of the experiment fish fed on diets having more than 40% of protein displayed significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 37 publications
2
20
1
Order By: Relevance
“…The results obtained in this study are consistent with the one reported by Johnston et al (2002) who observed an increased of growth by fibre recruitment when testing two dietary protein levels (high and low) on Atlantic salmon. Furthermore, Silva et al (2009a) have found an increase in muscle fibre recruitment when P. bogaraveo juveniles were fed high protein diet.…”
Section: Discussionmentioning
confidence: 96%
“…The results obtained in this study are consistent with the one reported by Johnston et al (2002) who observed an increased of growth by fibre recruitment when testing two dietary protein levels (high and low) on Atlantic salmon. Furthermore, Silva et al (2009a) have found an increase in muscle fibre recruitment when P. bogaraveo juveniles were fed high protein diet.…”
Section: Discussionmentioning
confidence: 96%
“…White muscle cellularity (number and size of muscle fibers) is a highly plastic process that depends both on intrinsic factors such as species and strain (e.g., Weatherley et al 1988;Valente et al 1999) and extrinsic factors that include temperature and exercise (for a review, see Johnston 2006), plane of nutrition (e.g., Weatherley et al 1979;Kiessling et al 1991;Salze et al 2014) and dietary nutrient composition (e.g., Fauconneau et al 1997;Alami-Durante et al 1997, 2010a, 2010bJohnston et al 2002;Silva et al 2009); it also follows seasonal cycle patterns (Alami-Durante et al 2007) and is strongly linked to the stage of development (for a review, see Johnston 1999). Most importantly, muscle cellularity is strongly correlated with the final size that a fish may attain.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a lot of studies were undertaken to compare sensorial and nutritional aspects of the main farmed fish species to their wild counterpart (Grigorakis, 2007;Periago et al, 2005;Sveinsdóttir et al, 2009). Farming techniques including environment salinity and temperature, rearing density, feeding procedures or slaughtering conditions were also extensively investigated and correlated to growth and quality criteria (Andrew, Holm, & Huntingford, 2004;Bagni et al, 2007;Calabretti, Cateni, Procida, & Favretto, 2003;Eroldogan, Kumlu, & Aktas, 2004).…”
Section: Introductionmentioning
confidence: 99%